BRANDING PERPUSTAKAAN MELALUI AKUN INSTAGRAM DALAM MENUNJANG BAURAN PEMASARAN DIGITAL DI GRHATAMA PUSTAKA YOGYAKARTA - Adzkiyah Mubarokah; Nurdin Laugu (Departemen Sastra Indonesia, Fakultas Sastra, Universitas Negeri Malang (UM), 2023)
A library as an information center has innovated in branding libraries through social media, one of which is through Instagram. This article discusses the branding carried out by the library through the Instagram account @Balaiyanpus.Dpaddiy in an effort to support the digital marketing mix at Grhatama Pustaka Yogyakarta. This research uses qualitative methods with a descriptive approach through field research methods. Research data were obtained from interviews with informants, literature reviews, and documentation. This study found the results that Grhatama Pustaka's Instagram has supported the marketing mix, judging from the SOSTAC (Situation Analysis, Objectives, Strategy, Tactics, Actions, Control) theory. The first aspect of situation analysis on the indicators that are the reference is four, namely customer insight, competitor analysis, and current channel, as well as using SWOT analysis has been fulfilled, the second aspect of the objectives indicators that have not been met, namely on unmeasured goals, the third aspect of strategy has also been fulfilled, the fourth aspect of tactics using the 7P marketing mix theory, 7P indicators that are still constrained are indicators of people or people who are still lacking, the fifth aspect of actions where indicators that have not been fulfilled, namely unstructured program planning carried out in writing and the sixth aspect of control monitored has been carried out by Grhatama Pustaka Yogyakarta